An update in the endoscopic management of gastric cancer. Issue 6 (November 2016) - Han, Samuel; Hsu, Andrew; Wassef, Wahid Y.
Abstract : Purpose of review: Gastric cancer remains a leading cause of mortality worldwide and gastroenterologists are playing an increasingly larger role in its management. This article reviews the endoscopic management of gastric cancer, with emphasis on recent advances in the field. Recent findings: Long-term studies comparing surgery and endoscopic resection for early gastric cancer have shown no difference in 10-year survival rates. Second-look endoscopy, performed 2 days after endoscopic submucosal dissection (ESD) to address the concern of delayed bleeding, may not affect rebleeding rates. Magnesium, proton pump inhibitors, and bupivacaine may help reduce post-ESD pain. New devices such as the Clutch Cutter and EndoLifter may help make ESD easier and safer. Summary: Endoscopic therapy for early gastric cancer is becoming increasingly popular and innovations are constantly being made to improve technique and technology. This review focuses on the latest approaches to the endoscopic management of gastric cancer. Abstract : Supplemental Digital Content is available in the text